Grenada Reconsidered - Hardt, D. Brent (Tufts Archival Research Center, 2005)
Volume 11, Issue 2. Summer In the first American military intervention since the Vietnam War, U.S. and Caribbean troops invaded Grenada in October 1983, overthrowing a Marxist military junta and restoring democratic government. The invasion provoked considerable controversy in the United States, but often forgotten or overlooked by both supporters and opponents of the action was that the decision to invade was not made unilaterally. Rather, as D. Brent Hardt argues, Grenada's neighbors in the eastern Caribbean played a major role in initiating the intervention. According to Mr. Hardt, the Reagan administration probably would not have intervened in the absence of Caribbean support. This multilateral character of the intervention, he concludes, made it a political success in Grenada, the Caribbean, and the United States.